2015
DOI: 10.1038/jid.2015.204
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Surface CD74–MIF Interactions Drive Melanoma Survival in Response to Interferon-γ

Abstract: While melanoma is believed to be a highly immunogenic tumor and recent developments in immunotherapies are promising. Interferon-γ (IFN-γ) produced by immune cells plays a crucial role in tumor immune surveillance; however, it has also been reported to be pro-tumorigenic. In the current study, we found that IFN-γ enhances the expression of CD74, which interacts with its ligand, macrophage migration inhibitory factor (MIF), and thereby activates the PI3K/AKT pathway in melanoma, promoting tumor survival. IFN-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 38 publications
3
76
0
Order By: Relevance
“…Although many markers have been noted extensively in the literature, in melanoma we have identified inflammatory cytokines IL-1α IL-1β and IL-6 (29) but none of these proved prognostic in our controlled and parallel studies shown here. In a previous functional study we observed that an MIF-CD74 autocrine interaction upregulated by exogenous IFN-γ, promoted the phosphorylation of AKT Ser473 and drove expression of such inflammatory cytokines (30), presenting a potentially protumor circuitous or alternative function when MIF is present, which may be likely in a subset of tumors after exposure to IFN-γ. These findings could be specifically important as we observed this effect regardless of the BRAF and NRAS mutation status.…”
Section: Discussionmentioning
confidence: 96%
“…Although many markers have been noted extensively in the literature, in melanoma we have identified inflammatory cytokines IL-1α IL-1β and IL-6 (29) but none of these proved prognostic in our controlled and parallel studies shown here. In a previous functional study we observed that an MIF-CD74 autocrine interaction upregulated by exogenous IFN-γ, promoted the phosphorylation of AKT Ser473 and drove expression of such inflammatory cytokines (30), presenting a potentially protumor circuitous or alternative function when MIF is present, which may be likely in a subset of tumors after exposure to IFN-γ. These findings could be specifically important as we observed this effect regardless of the BRAF and NRAS mutation status.…”
Section: Discussionmentioning
confidence: 96%
“…By immunohistochemistry, CD74 staining was observed to be co-localized with CD44 in some epithelial cells lining the BC in ADR-injured glomeruli, suggesting a role for CD74 expression in PEC activation. Although recent studies have suggested possible roles for the CD74-CD44 receptor complex and its ligand MIF in tumor cell proliferation [13,14,15,16], their roles in kidney diseases have not been elucidated; therefore, we attempted to evaluate CD74 expression in PEC activation and performed comparative analysis of CD74 and other PEC markers.…”
Section: Discussionmentioning
confidence: 99%
“…CD74 acts as a cell membrane receptor for the macrophage migration inhibitory factor (MIF), and the formation of the CD44-CD74 complex initiates the signaling pathway triggered by MIF in macrophages [9] and B cells [10,11,12], inducing cell proliferation and survival. Moreover, several studies suggested a role for CD74 expression in the progression of thyroid, breast, pancreatic, skin and gastrointestinal tract cancers [13,14,15,16]; however, only a few studies were conducted to evaluate the role of CD74 expression and that of CD74-CD44 complex in kidney diseases [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous findings that IFN‐γ upregulates both PD‐L1 and cell surface CD74 expression, we hypothesized that the MIF‐CD74 interaction mediated the expression of PD‐L1 after stimulation by IFN‐γ. To test this hypothesis, we treated 2 melanoma cell lines, A375 and SB2, with IFN‐γ and an antagonist of the MIF‐CD4 interaction, 4‐IPP.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous analysis of melanoma patient samples, serum IFN‐γ levels and CD74 expression levels in tumor cells showed a significant correlation. In addition, treating melanoma cell lines with recombinant IFN‐γ protein resulted in upregulation of cell surface CD74 protein levels …”
Section: Introductionmentioning
confidence: 99%